Caffeine antiplasticization of amorphous poly(ethylene terephthalate): Effects on gas transport, thermal, and mechanical properties. (18th May 2015) - Burgess, Steven K.; Lee, Jong Suk; Mubarak, Christopher R.; Kriegel, Robert M.; Koros, William J.
Abstract: This study investigates the phenomenon of caffeine antiplasticization of amorphous poly(ethylene terephthalate) (PET). Oxygen and carbon dioxide permeation measurements at 35 °C reveal significant barrier improvement (e.g., >3× for PET mixed with ∼10.7 wt% caffeine) for all PET/caffeine samples studied. Penetrant solubility and diffusivity estimates are used to deconvolute the relative transport contributions to the overall barrier reduction determined via permeation testing. Density values provide a direct measure of the reduced free volume for the antiplasticized samples vs. neat PET, and provide a basis for understanding the barrier improvement. Further investigation via dynamic mechanical analysis of the sub-ambient beta relaxation reveals that the diffusion reductions for the antiplasticized samples originate from caffeine suppressing the phenyl ring flipping mechanism known to occur in glassy PET. The data reported in this paper suggest that antiplasticization of PET occurs via a combination of both "hole filling" and chain mobility restriction mechanisms, and that the relative mechanistic contributions to transport reduction depend largely on the penetrant solubility and diffusivity within the polymer matrix. Graphical abstract: Highlights: Caffeine antiplasticization of amorphous PET was studied using various techniques. PET mixed with 10.7 wt% caffeine exhibits >3× transport reductions vs. PET. Antiplasticization affects diffusion more significantly than penetrant sorption. Caffeine was observed to hinder the phenyl ring flipping motions in PET via DMA. Antiplasticization occurs via hole filling and chain motion restriction mechanisms.